Suez canal - Arnoux, Hippolyte (1880)
The Suez Canal (Arabic: قناة السويس‎ qanāt as-suwēs) is a sea-level waterway in Egypt, connecting the Mediterranean Sea to the Red Sea through the Isthmus of Suez. Constructed by the Suez Canal Company between 1859 and 1869, it officially opened on 17 November 1869. The canal offers watercraft a more direct route between the North Atlantic and northern Indian oceans via the Mediterranean and Red seas, thus avoiding the South Atlantic and southern Indian oceans and reducing the journey distance from the Arabian Sea to London, for example, by approximately 8,900 kilometres (5,500 mi).[1] (Wikipedia)